Effect of ultraviolet and ultrasound on newcastle disease virus - M. Y. AL-Attar (Iraqi Journal of Veterinary Sciences, 2007)
The effect of ultraviolet irradiation on Newcastle disease virus( virulant and vaccinial strains) was studied .Results showed decrease the titer of virulant strain about 1.5 Log 10 and 1.2 Log 10 at254and 366 nm respectively such effect was less on vaccinial strain .Haemagglutination (HA) activity of the same viruses was also studied and showed that HA titer of virulant NDV was decreased 1Log2 when treated at 254 nm and 366 nm , but vaccinial NDV was not affected at 366 nm. The effect of ultrasound on viability of same viruses showed that the titer of virulant NDV was decreased 2.5 Log 10 and 3.5 Log 10 when treated with ultasound at the frequency 14 Ampittute (AM) and 22(AM) respectivly but the vaccinial NDV was less affected .Both viruses were lost their HA activity completely at 22(AM) for one minute .